The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1002/ptr.2120
|View full text |Cite
|
Sign up to set email alerts
|

Differential growth inhibitory effects of W. somnifera root and E. officinalis fruits on CHO cells

Abstract: The Chinese Hamster ovary (CHO) cell line is widely used for measuring drug cytotoxicity and resistance. Therefore, the effects of two major Ayurvedic drugs (W. somnifera root and E. officinalis fruits) on the short and long-term growth of these cells were investigated. A standard 96-well plate assay was used to measure short-term growth. For assessment of long-term growth, the colony formation assay (CFA) was used, which measures clonogenic potential. This assay is the best measure of the cytotoxicity of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 6 publications
(9 reference statements)
1
9
0
Order By: Relevance
“…This assay is based on cell metabolic activity where the reduction of yellow tetrazolium salt to orange formazan dye only occurs in viable cells by mitochondrial dehydrogenases; this can be measured by absorbance. It is important to bear in mind that the XTT assay aims to demonstrate immediate cytotoxic effect on cultured cells, whereas the clonogenic survival assay shows whether other damage has occurred to cells that interfere with or stop their proliferative capacity at a later time (Sumantran et al, 2007). The results of this study showed the absence of cytotoxic effects from HA/ PLGA and Bonefill ® eluates, which are in accordance with literature demonstrating HA, bovine bone, and PLGA as biocompatible materials (Galia et al, 2008;Cieślik et al, 2009;Trif et al, 2015).…”
Section: Resultssupporting
confidence: 89%
“…This assay is based on cell metabolic activity where the reduction of yellow tetrazolium salt to orange formazan dye only occurs in viable cells by mitochondrial dehydrogenases; this can be measured by absorbance. It is important to bear in mind that the XTT assay aims to demonstrate immediate cytotoxic effect on cultured cells, whereas the clonogenic survival assay shows whether other damage has occurred to cells that interfere with or stop their proliferative capacity at a later time (Sumantran et al, 2007). The results of this study showed the absence of cytotoxic effects from HA/ PLGA and Bonefill ® eluates, which are in accordance with literature demonstrating HA, bovine bone, and PLGA as biocompatible materials (Galia et al, 2008;Cieślik et al, 2009;Trif et al, 2015).…”
Section: Resultssupporting
confidence: 89%
“…Moreover, cell numbers were significantly reduced on exposure to positive control camptothecin at 0.1 μM as depicted in Figure b, whereas the cell number observed was higher in the case of NDRM as compared to nHA (Figure c), indicating the cell survival and viability of normal cells on treatments. Colony formation was reported as an in vitro quantitative technique to look at the potential of a single cell to grow into a large colony through clonal expansion . This assay also measures cell survival, and it is normally employed as a sensitive model for measuring long-term cytotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 11(b) shows the surviving fraction obtained by the clonogenic cell survival assay of the β-TCP/ MCPM and β-TCP/MCPM/Si cements. This assay measures the proliferative ability of single cells to form a colony and is routinely used as a sensitive model for assessing long-term cytotoxicity [38]. Considering the XTT results, CHO-K1 cells treated with C1 and C2 exhibited a proliferation rate lower than the NC.…”
Section: Resultsmentioning
confidence: 99%